How to support teenagers in social media utilization: based on mother's experience - Ira Kusumawaty; Fadly; Tri Basuki Kurniawan; Yunike (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
The complexity and vulnerability of physical, psychological and social conditions result in the possibility of adolescents slumping in the circumstance of social media addiction in the existing era of digitalization. The problem of mother’s support to adolescents is very complex and undeniably becomes very necessary in directing teenagers throughout the utilization of social media. However, research related to the assistance of a mother towards adolescents in accompanying social media is still highly restricted. This study intends to explore forms of mother assistance to adolescents in utilizing social media based on their experiences. This qualitative study applied a phenomenological approach, involving twelve mothers with adolescent children and determined based on purposive sampling techniques. Data collection is done through in-depth interviews and compiled into transcripts, further determining the code, categories, and themes. The analysis process uses Colaizzi method, so that after the theme is formulated, the validation of the theme by participants is carried out. Trustworthiness, peer de briefing is conducted to ensure the validity of research results. The three themes produced related to the mother's experiences in accompanying adolescents are educating themselves, openness in communicating and formulating a mutual commitment. It can be concluded that the mother is a strong figure in keeping teenagers from falling into the heartbreaking condition of social media addiction. It is recommended that social media addiction prevention programs be developed through the coordination of families, teachers and peers based on the policies of the education department.